2019
DOI: 10.1007/s00204-019-02552-0
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput confocal imaging of differentiated 3D liver-like spheroid cellular stress response reporters for identification of drug-induced liver injury liability

Abstract: Adaptive stress response pathways play a key role in the switch between adaptation and adversity, and are important in druginduced liver injury. Previously, we have established an HepG2 fluorescent protein reporter platform to monitor adaptive stress response activation following drug treatment. HepG2 cells are often used in high-throughput primary toxicity screening, but metabolizing capacity in these cells is low and repeated dose toxicity testing inherently difficult. Here, we applied our bacterial artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 56 publications
(78 reference statements)
0
44
0
Order By: Relevance
“…There is evidence to suggest that HepG2 cells cultured in 3D spheroids results in decreased proliferation and reduced reliance on glucose (Hiemstra et al 2019 ). Thus, we investigated if HepG2 3D spheroids had an increased sensitivity to the ETC inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence to suggest that HepG2 cells cultured in 3D spheroids results in decreased proliferation and reduced reliance on glucose (Hiemstra et al 2019 ). Thus, we investigated if HepG2 3D spheroids had an increased sensitivity to the ETC inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, culturing HepG2 as 3D spheroids sensitised the cells to OCR inhibition in the presence of glucose. Previous studies have demonstrated that 3D spheroid culture of HepG2 cells decreases proliferation, increases differentiation and increases sensitivity to various compounds with human drug-induced liver injury liability (Ramaiahgari et al 2014 ; Hiemstra et al 2019 ). Taken together, the data suggest that proliferating cells are less reliant on oxidative phosphorylation as an energy source where glucose is not limiting and that 3D HepG2 cells switch towards an oxidative phosphorylation-mediated energy source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpler test systems were combined to obtain advanced complex test systems to better resemble the in vivo situation. These approaches include, for instance, the use of mixed cell cultures (Gutbier et al 2018 ), 3D organoids and neurospheres (Brull et al 2020 ; Hiemstra et al 2019 ; Kobolak et al 2020 ) and microphysiological systems (MPS), e.g. four-organ-chips developed to interconnect miniaturized human intestine, liver, brain and kidney equivalents (Ramme et al 2019 ) and improved iPSC cell differentiation to hepatocytes (Boon et al 2020 ).…”
Section: The Repository Of Nams Available For Nam-enhanced Raxmentioning
confidence: 99%
“…Supporting our observation in hiPSC hepatic organoids, recent reports in HepG2 and rat primary hepatocytes have shown that hepatic genes such as PROX1, HNF4α, and C/EBPα are induced in 3D hepatocyte cultures. (48,49) TRIB1 liver-specific KO mice has increased C/EBPα protein (due to reduced protein degradation) and decreased C/EBPα transcript (due to negative feedback from the increased protein). (23) We also know that TRIB1 is a transcriptional target of C/EBPα, leading to a negative feedback loop in which excess C/EBPα induces TRIB1, which then promotes the degradation of C/EBPα.…”
mentioning
confidence: 99%